Are African rural youth innovative? Claims, evidence and implications. (July 2019) - Sumberg, James; Hunt, Stephen
Abstract: Claims about the innovativeness and creativity of African rural youth are frequently made in policy discourse. These claims feed a smart economics investment logic and help guide serious resource allocation and programming decisions. Yet, as demonstrate in this paper, they reflect essentialist thinking and there is little evidence to support them. The paper argues that if Africa′s youth bulge and potential demographic dividend are as important as commonly stated, it should be a first priority of all development partners to carefully assess the claims they make about rural youth and that focus and orient their actions, and those of others. Highlights: The claim that African rural youth are innovative is integral to policy discourse. This claim influences resource allocation and choice of interventions. There is little evidence to support this claim. Alternative justifications for investing in Africa′s rural youth are needed.